2021
DOI: 10.5617/osla.8493
|View full text |Cite
|
Sign up to set email alerts
|

Helt sjukt å være så jævlig god. Bruk av adjektivforsterkere i moderne norsk

Abstract: Intensifiers are described in several recent articles as unstable vocabulary elements. This article presents an investigation of intensifiers of adjectives in four Norwegian corpora of speech language and two of written language, which shows that some intensifiers are rapidly increasing in use and others declining. An adjectival intensifier does strengthen or underline the meaning of the adjective, but is also an important mean to show the speaker’s opinions or attitude to what is described. The investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…2 (1) a. det er jo drittdårlig 3 it is PTCL Relative to the number of studies on intensifiers in English, work on Norwegian intensifiers is underrepresented in research on language variation and change, and, to date, there have been no variationist sociolinguistic analyses of the Norwegian intensifier system. To the best of our knowledge, previous literature is limited to a small number of master theses (Bardas 2008, Westervoll 2015, Wilhelmsen 2019), a recent corpus-based sociolinguistic analysis (Fjeld 2020), and a limited number of descriptive and formal semantic works (Skommer 1993, Livanova 1997, Svenonius & Kennedy 2006, Ebeling & Ebeling 2015. Skommer (1993) examined the use of morphological intensification in Norwegian, focusing on semantic denotation.…”
Section: Norwegian Intensifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…2 (1) a. det er jo drittdårlig 3 it is PTCL Relative to the number of studies on intensifiers in English, work on Norwegian intensifiers is underrepresented in research on language variation and change, and, to date, there have been no variationist sociolinguistic analyses of the Norwegian intensifier system. To the best of our knowledge, previous literature is limited to a small number of master theses (Bardas 2008, Westervoll 2015, Wilhelmsen 2019), a recent corpus-based sociolinguistic analysis (Fjeld 2020), and a limited number of descriptive and formal semantic works (Skommer 1993, Livanova 1997, Svenonius & Kennedy 2006, Ebeling & Ebeling 2015. Skommer (1993) examined the use of morphological intensification in Norwegian, focusing on semantic denotation.…”
Section: Norwegian Intensifiersmentioning
confidence: 99%
“…He found that så 'so', for 'too', and helt 'completely' were the three most frequently used Norwegian variants. In a corpus-based analysis, which included both spoken and written data, Fjeld (2020) found that veldig 'very' and jaevlig 'very' were the most frequent variants. However, because of the methodological decision to measure frequency by normalizing and comparing the absolute frequency with the number of words per corpus, the analysis was unable to determine whether women were more likely to intensify than men and whether intensifier choices differed by gender.…”
Section: Norwegian Intensifiersmentioning
confidence: 99%
See 1 more Smart Citation